Training of education researchers in Peru: contexts and challenges - Turpo-Gebera, Osbaldo; Díaz-Zavala, Rocío; Pérez-Postigo, Gerber; Cuadros-Paz, Luis; Esquivel Las Heras, Janeth (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
A multiplicity of contexts associated with the university mission converge in the training of educational researchers. From this perspective, it is essential to analyze the positions of educational researchers regarding their identity, training and development. In this sense, the focus group technique was used, involving thirteen researchers in training, with diverse trajectories. The analyzed discourses show identity dualities, both of academic recognition and social commitment, as well as formative alternations in research that place the university as the hegemonic formative space; and spaces of formative development that lead to value between scientific products or social impacts.